Pre-departure psychological distress, depression, anxiety, stress and perception of risk factors at workplace among migrant workers of Nepal: A pilot study - Poudel, Om Prakash; Thapa, Bijay; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2019)
Introduction: Migration is a stressful process and perception regarding risk factors at workplace can impact the mental health of migrant workers early from pre-departure phase. Around 23% percent of returnee migrants of Nepal reported having mental problems. Yet, only few researches were conducted on the mental health of Nepali migrant workers during pre-departure phase and this study aims to fill that gap.Method: A cross-sectional study was conducted on 39 migrant workers during the pre-departure phase to measure the level of psychological distress, depression, anxiety and stress. It was also used to validate the locally developed pre-departure risk factor perception scale (PD-RFPS) at workplace. Validated DASS-21 and PD-RFPS tools in Nepali language were self-administered in two pre-departure orientation institutes of Kathmandu valley. Consensus index was used to summarize the perception of migrant workers on the possible risk factors at workplace.Result: Prevalence of psychological distress, depression, anxiety and stress were identified as 28.21%, 35.9%, 41.03% and 20.51% respectively. The DASS-21 scale and sub-scales were found to have good internal consistencies. DASS-Depression and DASS-Anxiety subscales showed concurrent validity with Beck’s Depression Inventory (BAI) and Beck’s Anxiety Inventory (BAI). The PD-RFPS tool also showed good internal construct reliability. Migrant workers perceived differently about the risk factors at workplace as consensus index ranged between 41.61% and 73.96%.Conclusion: Prevalence of psychological distress, depression, anxiety and stress among the migrant workers at pre-departure phase suggests the presence of symptoms of mental health problems. It also warrants further study with large sample size and representative sampling methods.